IMPLEMENTASI FUZZY INFERENCE SYSTEM (FIS) METODE SUGENO DALAM PROSES PENYIANGAN KOLEKSI BUKU PERPUSTAKAAN (STUDI KASUS : PERPUSTAKAAN UNIVERSITAS INDONESIA) - Siti Sakinah (2020)
This research was conducted to create a web-based application system that can simplify the process of weeding book collections at the University of Indonesia Library. That is because the weeding process is one of the activities that are not easy to do. Librarians must seriously consider library materials to be weeded to prevent mistakes and complaints from stakeholders. The algorithm applied to this application system is the Sugeno Fuzzy Inference System (FIS) method. There are 3 aspects of valuation that are used as input variables in the weeding process, namely book condition, lending circulation, and book inventory (number of copies). Of the 3 input variables, 27 are fuzzy rule-based, which form the basis of linguistic rules to describe the correlation between input parameters and expected output. The output produced in this study is to determine suggestions for the collection of library books divided into 4 that should be withdrawn, should be replaced, should be donated, and should still be displayed. From the tests that have been carried out on the book titled "Invention of Customary Laws" with Book Conditions valued at 6, Loan Circulation valued at 8 and Book Inventories valued at 25 produce a final score of 0.75 where the output is the book "should be granted."